Efficacy of an elasto-flexible morphing wing at high lift using fluid-structure-interaction simulations - Pflüger, J.; Von Langsdorff, M.; Breitsamter , C. (Frontiers in Aerospace Engineering, 2022)
The wide field of applications is the driving force behind the scientific interest in unmanned and micro air vehicles. For these aircraft, morphing wing technologies offer the possibility to adapt the aerodynamics to different flight stages. A morphing wing configuration with two elasto-flexible membrane wings is investigated numerically at a low Reynolds number of Re = 264000. The concept enables wing folding over a wide range and it allows the wing to adapt to changing aerodynamic loads. The focus is set on the benefits of the membrane in the high lift regime. Therefore, fluid-structure-interaction simulations are performed for the model equipped with a flexible and with a rigid wing. The comparison of the numerical results to data from previous experimental measurements show a good agreement. Compared with the rigid wing, the elasto-flexible membrane increases the gradient in the linear region and the maximum lift coefficient. In addition, the maximum lift coefficient is shifted to higher angles of attack. For selected wing positions and angles of attack, the aerodynamic behavior of the flexible and the rigid wing are investigated by means of the lift coefficient, the deformation of the membrane, the wall shear stresses and the wing surface pressure distribution. The deformation of the wing surface directly influences the area of flow separation at the extended wing and the separating leading-edge vortex at the folded wing. Both effects increase the generated lift of the wing with a flexible membrane.